2009
DOI: 10.1103/physrevd.80.084033
|View full text |Cite
|
Sign up to set email alerts
|

de Sitter spacetimes with torsion in the model of de Sitter gauge theory of gravity

Abstract: In the model of de Sitter gauge theory of gravity, the empty homogenous and isotropic spacetimes with constant curvature scalar and nonvanishing homogenous and isotropic torsion must have de Sitter metrics. The static de Sitter spacetime with static, O(3)-symmetric, vector torsion is the only spherically symmetric, vacuum solution with the metric of the form g µν = diag(A 2 (r), −B 2 (r), −r 2 , −r 2 sin 2 θ). The expressions of the torsion for different de Sitter spacetimes are presented. They are different f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Although the different dS spacetimes with nonzero torsion in the model have been obtained in Refs. [14,15], they are still not the S-dS solutions. For many quadratic models of gauge theory of gravity, S-dS solutions with spherically symmetric torsion have been given [16], but our model does not fall into those cases.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the different dS spacetimes with nonzero torsion in the model have been obtained in Refs. [14,15], they are still not the S-dS solutions. For many quadratic models of gauge theory of gravity, S-dS solutions with spherically symmetric torsion have been given [16], but our model does not fall into those cases.…”
Section: Introductionmentioning
confidence: 96%
“…In the second case (Case B), the metric and torsion fields are not required to be differentiable with respect to Λ. The reason to relax the differentiability condition is that there exist indeed the dS spacetimes with torsion, where the torsion fields are not differentiable with respect to Λ at the point Λ = 0 [14]. In this case, the computation is simplified by means of setting Λ → 0 in the weak field approximate equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ubiquitous feature of gauge-gravity theories is manifolds with non-vanishing torsion. When models based on the Poincaré [14] or de Sitter groups [15,16] were applied in cosmology, it was found that nonzero torsion can drive late time acceleration. Actually, in the de Sitter case nonzero torsion is a necessary condition for the existence of non-radiation cosmological matter.…”
Section: Introductionmentioning
confidence: 99%
“…The different de Sitter spacetimes with nonzero torsion in the dS gravity have been presented in Ref. [38]. It has also been shown that all vacuum solutions of Einstein field equations with a cosmological constant are the vacuum solutions of the set of field equations without torsion [32][33][34]37].…”
mentioning
confidence: 99%